Treatment and prevention of HIV infection with long-acting antiretrovirals. Issue 5 (4th May 2018) - Benítez-Gutiérrez, Laura; Soriano, Vicente; Requena, Silvia; Arias, Ana; Barreiro, Pablo; de Mendoza, Carmen
ABSTRACT: Introduction : Current antiretroviral therapy allows to achieve and sustain maximal suppression of HIV replication in most treated patients. As result, the life expectancy of HIV-infected persons has improved dramatically and is nowadays similar to that of the HIV-negative population. However, oral antiretrovirals have to be taken daily and indefinitely to avoid resumption of HIV replication and selection of drug resistance. Unfortunately, drug adherence is often suboptimal and tends to decline over time. Areas covered : New drugs, formulations and delivery systems are being developed for extended-release of antiretrovirals. At this time, intramuscular cabotegravir and rilpivirine, dapivirine vaginal rings and tenofovir alafenamide subdermal implants are the products in more advanced stages of clinical development. Their pharmacokinetics/dynamics and safety/efficacy are reviewed. Expert commentary : In the absence of eradicative therapy for individuals with HIV infection and protective vaccines for persons at risk, long-term antiretroviral therapy is the best approach for preventing disease progression in patients and halting transmissions, either as result of 'treatment as prevention' for HIV carriers or 'pre-exposure prophylaxis' for uninfected individuals at risk. In all these scenarios, the advent of long-acting antiretrovirals will expand options for overcoming the challenge of suboptimal drug adherence and reduce the burden of HIV infection.